The role of vitamin D in sleep regulation: mechanisms, clinical advances, and future directions - Cai, Zhilong; Rui, Shuoyu; Huang, Nanqu; Feng, Fei; Luo, Yong (Frontiers in Nutrition, 2025)
Vitamin D, an essential neuroendocrine regulator, exhibits a significant dose-dependent association with various sleep disorders according to epidemiological evidence, and plays a multifaceted and critical role in sleep regulation. This review summarizes the molecular mechanisms, clinical applications, and future directions of vitamin D in sleep regulation. Vitamin D may influence sleep through multiple molecular pathways, including modulation of neurotransmitter systems, maintenance of circadian rhythms, and neuroimmune regulation. Clinical trials have demonstrated that vitamin D supplementation significantly improves sleep quality, particularly in special populations such as the elderly and pregnant women. However, challenges persist in optimizing individualized treatment regimens, developing novel drug delivery systems, and evaluating long-term efficacy. The integration of multi-omics analyses and artificial intelligence offers innovative solutions to these challenges. Future research should focus on elucidating the precise molecular mechanisms of vitamin D in sleep regulation, refining personalized therapeutic strategies, and advancing innovative delivery systems to enhance the prevention and treatment of sleep disorders.